Eight‐Fold Increase in Dietary Supplement–Related Liver Failure Leading to Transplant Waitlisting Over the Last Quarter Century in the United States. Issue 2 (27th November 2021) - Ghabril, Marwan; Ma, Jiayi; Patidar, Kavish R.; Nephew, Lauren; Desai, Archita P.; Orman, Eric S.; Vuppalanchi, Raj; Kubal, Shekhar; Chalasani, Naga
Abstract : We investigated the trends in listing and outcomes of drug‐induced acute liver failure (DIALF) over the last quarter century in the United States using the United Network for Organ Sharing (UNOS) database. We examined waitlisted patients in the UNOS database between 1995 and 2020 with a diagnosis of DIALF and assessed trends in etiologies, demographic and clinical characteristics, and outcomes over 3 periods: 1995‐2003, 2004‐2012, and 2013‐2020. Patients with DIALF and cirrhosis were classified as drug‐induced acute‐on‐chronic liver failure. Implicated agents including acetaminophen (APAP) and herbal or dietary supplements (HDSs) were ascertained. There were 2146 individuals with DIALF during the study period. The observed demographic trends between the earliest and latest period included fewer pediatric patients (18.8% to 13.5%) but with an increasing number of males in non‐APAP DIALF (31.8% to 41.4%) and increased racial diversity in APAP DIALF. Antimicrobials remained the most common non‐APAP agents across all periods, but antiepileptics, propylthiouracil, and mushroom poisoning decreased, while HDSs markedly increased from 2.9% to 24.1% of all non‐APAP DIALF patients. The overall 5‐year post‐liver transplantation (LT) patient survival improved significantly over the 3 periods (69.9% to 77.4% to 83.3%) and was evident for both APAP and non‐APAP DIALF. Over the last quarter century, there has been an 8‐fold increase in HDS‐related liver failure necessitating waitlisting for liver transplantation in the United States. There are other important temporal trends during the study period, including improved survival following LT among both APAP and non‐APAP DIALF patients.